Analysis Of Machine Maintenance Using Markov Chain Method For Reducing Maintenance Cost - Setya Adi Pratama; Boy Isma Putra (Universitas Muhammadiyah Sidoarjo, 2022)
PT. Steel Pipe Industry of Indonesia, Tbk. (SPINDO Unit IV) is a company engaged in manufacturing welding spiral pipe production. In 2021 there was an increase in maintenance costs compared to 2020, which in 2020 amounted to Rp 3.051.800.000 to Rp 3.299.400.000 in 2021, which mean an increase of Rp 247.600.000 or 8%. Based on those problems, the purpose of this study is to determine the policies that should implemented to reduce maintenace costs. The method used is markov chain method. By using the markov chain method, it can be determined the best policy that can lead to lower maintenance costs, whether preventive maintenance or corrective maintenance. So that the company can determine the best maintenance policy for the future. The result obtained from using the markov chain method for this research are that the results can saving of Rp 680.000.000 compared to initial maintenace costs.